Perhydroxylcucurbit[6]uril as a highly selective gas chromatographic stationary phase for analytes of wide‐ranging polarity. Issue 5 (19th January 2015) - Sun, Tao; Qi, Meiling; Fu, Ruonong
<x xml:space="preserve">Abstract</x> This work describes the separation performance of a perhydroxylcucurbit[6]uril stationary phase for capillary gas chromatography. The perhydroxylcucurbit[6]uril stationary phase exhibits higher resolving capabilities for critical analytes with better peak shapes than cucurbit[6]uril and conventional stationary phases. The advantageous separation feature of the perhydroxylcucurbit[6]uril stationary phase may originate from its unique structure and favorably balanced interactions with the analytes. Also, the perhydroxylcucurbit[6]uril column shows good separation repeatability with relative standard deviations in the range of 0.01–0.13% for intraday, 0.37–0.82% for interday, and 1.0–4.7% for column‐to‐column repeatability.